Genetic analysis of a Mediterranean Red-Listed species Brachytrupes megacephalus (Lefèbvre, 1827) (Orthoptera, Gryllidae) - Bartolo, Angela G.; Cassar, Louis-F.; Massa, Bruno; Schembri, Sarah; Ghana, Salah (Zootaxa, 2025)
Brachytrupes megacephalus, the Giant Sand-dune Cricket, which has a restricted distribution across some locations in the Mediterranean and the more arid Sahara, typically colonises psammophilous biocoenoses within coastal and desert regions, including cultivated land where the substrate is characteristically sandy. Recent assessments reported that the species’ European population trend is in decline. Despite being a Red-listed species of conservation interest, it has not yet been studied genetically. The present study examines B. megacephalus specimens from Mediterranean locations in Sicily, Linosa, Sardinia, Malta, Gozo, and Libya, in addition to specimens of allied taxa from West Africa and the Far East. Barcode sequencing was carried out for fragments of the small (12SrRNA, 400 bp) and large (16srRNA, 500 bp) mitochondrial ribosomal subunits, the small nuclear ribosomal subunit (18SrRNA, 650 bp), the large nuclear ribosomal unit (28SA, 400 bp rRNA), the gene coding for H3 protein (H3, 330 bp) and cytochrome c oxidase subunit 1 (CO1 600 bp). Subsequent phylogenetic analyses supported this clade as separate (at species level) from Brachytrupes membranaceus, which is the only other congener for which sequence data exists in online DNA libraries.